Educators’ perspective on teachers’ beliefs as key-factors for the implementation of mathematics learning activities designed from an enactive-embodied approach - Boscolo, Alessandra (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
If we are interested in the implementation of research findings, as teaching practices, within school settings, it becomes crucial to outline what beliefs should guide teachers in implementing these findings from the researchers’ viewpoint. These beliefs essentially define the underlying philosophy behind these practices and offer valuable insights into how educators can facilitate teachers in bringing the research findings in schools. In our exploratory study, researchers from Italy and Australia hypothesized, specifically, potential beliefs of primary and secondary school mathematics teachers that can be related to the introduction and successful integration of mathematics learning activities designed from an enactive-embodied perspective. This constitutes a key preliminary step for exploring teacher beliefs by directly involving them in a survey.